Factors Affecting Treatment Persistence in Japanese Patients with Psoriasis Prescribed Biologics: A Real-World Study Using an Insurance Claim Database - Celine Miyazaki; Junya Masuda; Phiona I-Ching Tsai; Hidehisa Saeki (Adis, Springer Healthcare, 2024)
Abstract Introduction Poor persistence to biologics can result in suboptimal health outcomes and increased economic burden for chronic conditions, including psoriasis (PsO). In Japan, studies evaluating factors responsible for biologic treatment persistence in patients with PsO are limited. We assessed biologic treatment persistence (median treatment duration and overall treatment survival) and associated factors in patients with PsO in a real-world setting. Methods This retrospective analysis of insurance claims records from the Japan Medical Data Center (JMDC) database included patients with PsO [International Classification of Diseases (ICD) code: L40.x] ≥ 18 years of age who had received biologic treatment. Treatment persistence was analyzed using data from 2016 to 2020 by biologic class and by individual biologics (infliximab, adalimumab, ustekinumab, guselkumab, secukinumab, ixekizumab, and brodalumab) in bio-naïve (who initiate first biologic at index) and bio-experienced patients. Kaplan-Meier survival (treatment persistence), and multivariate Cox proportional hazard regression (predictive factors) analyses were used. Results Overall, 1528 patients with PsO were included (mean age 47.4 years). Infliximab had the longest median treatment duration (33.6 months), while brodalumab had the shortest (9.7 months) among biologics evaluated. Of the biologics evaluated, 1-year treatment survival was highest with guselkumab (83%), and lowest with brodalumab (45%). Bio-experienced patients showed slightly longer median treatment duration than bio-naïve patients (22.8 versus 18.1 months). Factors predictive of treatment persistence were sex [male; hazard ratio (HR) 0.84, p = 0.016] and specific PsO diagnostic codes, such as L40.0 (PsO vulgaris; HR 0.69; p = 0.006), L40.1 (generalized pustular PsO; HR 0.75; p = 0.034), and L40.9 (PsO unspecified; HR 0.72; p = 0.001). Meanwhile, age and Charlson Comorbidity Index score were significantly associated with adalimumab and infliximab treatment persistence, respectively. Conclusion Among biologics evaluated, infliximab had the longest median treatment duration, and guselkumab had the highest 1-year treatment survival. Sex and specific PsO diagnostic codes influenced overall treatment persistence. These findings could inform long-term treatment plans for PsO in real-world clinical settings.